1996
DOI: 10.1046/j.1365-2249.1996.d01-724.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neutrophil cytoplasmic antibodies (ANCA) in ulcerative colitis: anti-cathepsin G and a novel antibody correlate with a refractory type

Abstract: SUMMARYWe analysed the clinical significance of ANCA in patients with ulcerative colitis. On either an indirect immunofluorescence assay or an ELISA with fixed neutrophils, 71% (25/35) of the patients were positive for ANCA. However, only half of them reacted with either cathepsin G or lactoferrin. Western blot assays revealed positive bands in 40% (10/25) of the antibody-positive patients. The sizes of the bands detected were 58, 47, 44, 40, and 28 kD. No significant correlation was found between the ANCA pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
0
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 20 publications
7
29
0
3
Order By: Relevance
“…Th ese autoantigens are thought to be located not only in the cytoplasm of the granulocyte but also inside the granulocyte nucleus (histone 1, nonhistone chromosomal protein, high mobility group) [17,[27][28][29][30][31], with exhibited sensitivity on DNA-se treatment [17,27]. In agreement with the fi ndings of some other investigators [32][33][34], we found a positive reaction with cathepsin-G in two cases of UC; however, this specifi city was not signifi cantly diff erent from the control group, where two samples also tested positive with cathepsin-G. In our study we have confi rmed the previously reported specifi city of PAB for CD [18,35] and found PAB only among the patients with CD, but with a low prevalence (30%), comparable with the prevalences (26-39%) reported by other investigators [18,[35][36][37].…”
Section: Discussionsupporting
confidence: 68%
“…Th ese autoantigens are thought to be located not only in the cytoplasm of the granulocyte but also inside the granulocyte nucleus (histone 1, nonhistone chromosomal protein, high mobility group) [17,[27][28][29][30][31], with exhibited sensitivity on DNA-se treatment [17,27]. In agreement with the fi ndings of some other investigators [32][33][34], we found a positive reaction with cathepsin-G in two cases of UC; however, this specifi city was not signifi cantly diff erent from the control group, where two samples also tested positive with cathepsin-G. In our study we have confi rmed the previously reported specifi city of PAB for CD [18,35] and found PAB only among the patients with CD, but with a low prevalence (30%), comparable with the prevalences (26-39%) reported by other investigators [18,[35][36][37].…”
Section: Discussionsupporting
confidence: 68%
“…Thus, it appeared that an antibody against neutrophil 28-kD antigen serves as a predictive marker of refractory UC. Although the molecular size of the 28-kD protein was similar to that of cathepsin G, we proved that they were distinct from each other [9]. Here, we report the purification and identification of this protein.…”
Section: Introductionmentioning
confidence: 70%
“…Considering that previously identified P-ANCA in UC do not correlate with disease activity, duration, extent, or treatment [2,3,9], anti-HMG1/2 antibodies might become important in the serological diagnosis of refractory UC. It is also interesting that anti-HMG1/2 and anti-cathepsin G antibodies co-developed in patients with refractory UC [9]. To investigate the disease specificity of anti-HMG1/2 antibodies, screening of the antibodies by ELISA using HMG1 and HMG2 is underway.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations